PengaruhMotivasi,Kepuasan Kerja, Gaya Kepemimpinan, Kompensasi, dan Kemampuan Terhadap Kinerja Pegawai Akuntansi di Pemerintah Kabupaten Bengkalis (Studi Empiris pada SKPDKabupaten Bengkalis) - Annisa Rahmadita; Raja Adri Satriawan; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study aimed to examine the effect motivation, job satisfaction, leadership style, compensation, and ability to job performance of accounting personnel in the of Bengkalis. The results of this study were 1) Research that has een done, namely to 50 (fifty) of respondents who are employees of the accounting contained in the entire district on education in Bengkalis. 2) Validity and reliability te results indicate that all variables (motivation, job satisfaction, style of leadership, compensation, and abilities) valid and reliable. So also in the classical assumption test also showed normal distribution of data, not the autocorrelation and multicollinearity and also the has been no symptoms heteroskedastisitas. 3) Test results of hypothesis 1, 2, 3, 4, and 5 show the results are variable influence motivation, job satisfaction, style of leadership, compensation, and accounting capabilities to job performance of employee 4) From the regression test results can be seen in the level of influence of the independent variables (motivation, job satisfaction, leadership, compensation, and abilities) together in explaining th elationship to the dependent variable is the quality of the results of the examination has a lue of r2 = 0831 or 83.1% . While the adjusted r2 value of 0.811 or 81.1% means that the independent variable is able to fully explain the dependent variable is equal to 81.1%. out put disclaimer governmentKeywords: motivation, job of satisfaction, style of leadership, compensation, ability, and job performance